Implementasi Yuridis Keadilan Restoratif Dalam Penyelesaian Perkara Pidana Terhadap Penanganan Perkara Anak Yang Menjadi Korban Melalui Media Sosial Di Polres Ogan Ilir Dan Urgensinya (Berdasarkan Laporan Kepolisian Nomor LP/B/2/1/2024/SPKT/POLRES OGAN ILIR/POLDA SUMSEL) - Kesuma, Derry Angling (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The handling of criminal cases involving children as victims, especially in the context of crimes through social media, requires an approach that not only prioritizes formal legal aspects, but also considers the protection of children's rights. This research examines the juridical implementation of restorative justice in the settlement of criminal cases against child victims of cyber crime, with a case study based on Police Report No. LP/B/2/1/2024/SPKT/POLRES OGAN ILIR/POLDA SUMSEL. The research method used is empirical juridical approach with data collection through literature study and interviews with law enforcement officials at Ogan Ilir Police Station. The results showed that the application of restorative justice still faces various obstacles, both in terms of regulations, understanding of law enforcement officials, and the availability of supporting facilities such as professional mediators. However, this approach is considered urgent to implement, given the psychological and social impacts on child victims. Therefore, it is necessary to strengthen regulations and intensive training for law enforcement officials so that the application of restorative justice in similar cases can run effectively and in favor of the best interests of children.